Bintan Regency Government Strategy to Increase Tourism During the Pandemic - Khotimah, Nurul; Kismartini, Kismartini; Priyadi, Budi Puspo (KnE Social Sciences, 2022)
Tourism is a supporting sector of the economy because it provides a large foreign exchange contribution. Bintan makes tourism a leading sector of the region. However, Bintan tourism was badly affected by the pandemic, with 82% fewer visits, leading to a decline in PAD and economic growth rates. This study aimed to analyze the strategic steps taken by the Bintan Regency Government to generate tourism during the pandemic. This study used qualitative methods. Based on the research, it can be seen that the strategy taken by the Bintan Regency Government was to provide a sense of security in traveling (safe travel) because currently tourists need security and safety guarantees when traveling; also, the government provided free tax sanctions for businesses given the difficult economy, and changed the target market by aiming for opportunities to increase domestic tourist visits by providing various attractive promotions. Keywords: tourism, tourists, health protocol, Covid-19